Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's solve the equation [tex]\(\log_3(x+1) + \log_3(x-1) = 2\)[/tex] step by step.
1. Combine the Logarithms:
Using the property of logarithms that [tex]\(\log_b(a) + \log_b(c) = \log_b(ac)\)[/tex], we can combine the left side of the equation:
[tex]\[ \log_3((x+1)(x-1)) = 2 \][/tex]
2. Simplify the Argument:
Next, simplify the argument of the logarithm by multiplying the terms:
[tex]\[ (x+1)(x-1) = x^2 - 1 \][/tex]
So our equation now becomes:
[tex]\[ \log_3(x^2 - 1) = 2 \][/tex]
3. Rewrite in Exponential Form:
Express the logarithm equation as an exponential equation. Recall that if [tex]\(\log_b(a) = c\)[/tex], then [tex]\(a = b^c\)[/tex]. Thus:
[tex]\[ x^2 - 1 = 3^2 \][/tex]
Simplify [tex]\(3^2\)[/tex]:
[tex]\[ x^2 - 1 = 9 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
To find [tex]\(x\)[/tex], add 1 to both sides:
[tex]\[ x^2 = 10 \][/tex]
Now, take the square root of both sides:
[tex]\[ x = \pm \sqrt{10} \][/tex]
5. Verify Solutions:
It's important to check whether both solutions are valid in the context of the original logarithmic equation because the arguments of the logarithms must be positive.
- For [tex]\(x = \sqrt{10}\)[/tex]:
[tex]\[ x + 1 = \sqrt{10} + 1 > 0 \quad \text{and} \quad x - 1 = \sqrt{10} - 1 > 0 \][/tex]
Since both values are positive, [tex]\(x = \sqrt{10}\)[/tex] is valid.
- For [tex]\(x = -\sqrt{10}\)[/tex]:
[tex]\[ x + 1 = -\sqrt{10} + 1 < 0 \quad \text{(invalid because argument of log must be positive)} \][/tex]
Thus, [tex]\(x = -\sqrt{10}\)[/tex] is not valid because it causes the arguments of the logarithms to be non-positive.
Therefore, the only valid solution to the equation is:
[tex]\[ x = \sqrt{10} \][/tex]
1. Combine the Logarithms:
Using the property of logarithms that [tex]\(\log_b(a) + \log_b(c) = \log_b(ac)\)[/tex], we can combine the left side of the equation:
[tex]\[ \log_3((x+1)(x-1)) = 2 \][/tex]
2. Simplify the Argument:
Next, simplify the argument of the logarithm by multiplying the terms:
[tex]\[ (x+1)(x-1) = x^2 - 1 \][/tex]
So our equation now becomes:
[tex]\[ \log_3(x^2 - 1) = 2 \][/tex]
3. Rewrite in Exponential Form:
Express the logarithm equation as an exponential equation. Recall that if [tex]\(\log_b(a) = c\)[/tex], then [tex]\(a = b^c\)[/tex]. Thus:
[tex]\[ x^2 - 1 = 3^2 \][/tex]
Simplify [tex]\(3^2\)[/tex]:
[tex]\[ x^2 - 1 = 9 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
To find [tex]\(x\)[/tex], add 1 to both sides:
[tex]\[ x^2 = 10 \][/tex]
Now, take the square root of both sides:
[tex]\[ x = \pm \sqrt{10} \][/tex]
5. Verify Solutions:
It's important to check whether both solutions are valid in the context of the original logarithmic equation because the arguments of the logarithms must be positive.
- For [tex]\(x = \sqrt{10}\)[/tex]:
[tex]\[ x + 1 = \sqrt{10} + 1 > 0 \quad \text{and} \quad x - 1 = \sqrt{10} - 1 > 0 \][/tex]
Since both values are positive, [tex]\(x = \sqrt{10}\)[/tex] is valid.
- For [tex]\(x = -\sqrt{10}\)[/tex]:
[tex]\[ x + 1 = -\sqrt{10} + 1 < 0 \quad \text{(invalid because argument of log must be positive)} \][/tex]
Thus, [tex]\(x = -\sqrt{10}\)[/tex] is not valid because it causes the arguments of the logarithms to be non-positive.
Therefore, the only valid solution to the equation is:
[tex]\[ x = \sqrt{10} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.